Penyisipan Pesan dengan Metode Least Significant Bit Pada Objek Citra Digital Yang Terdeteksi Tepi Dengan Sobel - Sitio, Elfina Nanda (TIN: Terapan Informatika Nusantara, 2020)
Communication is very important in exchanging information and there are times when the information is very important and confidential. But the number of people who commit crimes to steal and leak information in the world of IT with various techniques.Such communication media are no longer safe to use, so the communication media must be increased in security. Based on this, the authors are interested in making an analysis of the application of the Least Significant Bit Method and edge detection with sobel on digital image objects. Least significance bit method and edge detection with sobel on digital image objects can make the size and shape of the image that has been inserted the message character will not change, so that the message or information sent has a higher level of security